The Consequences of Mergers, Acquisitions and Strategic Alliances in the Internet search and Navigation Services Industry: Case studies of Google and Yahoo! - Yiu, Hoi Man (2010)
This paper is focussed on finding motives and assessing the consequences of mergers, acquisitions and strategic alliances of two dominant players in the search engine industry – Google Inc. and Yahoo! Inc. It overviews a vast amount of theoretical literature on the companies’ incentives to engage in mergers’, acquisitions’ and strategic alliances’ and presents empirical literature financial findings of the company and its stock market’s post-merger performance. Case studies section of the dissertation examines the history and motives of Google and Yahoo! for engaging in such events, and measures the consequences of this activity by applying accounting and empirical financial approaches. Qualitative data is obtained from both online and published resources; the findings are that: